Pengembangan PowerPoint ISpring Suite pada Model Discovery Learning untuk Meningkatkan Motivasi dan Hasil Belajar: Development Of PowerPoint ISpring Suite on Discovery Learning Model to Improve Motivation and Learning Outcomes - Imanurahman, Annisa; Juniar, Juniar; Hardin, Hardin (Edu-Sains: Jurnal Pendidikan Matematika dan Ilmu Pengetahuan Alam, 2026)
The development PowerPoint  iSpring Suite with ADDIE development pattern (analysis, design, development, implementation and evaluate). This research aims to produce valid, practical, and effective products. The sources of data in this study are media experts and material experts as sources of validity test data, chemistry teachers 1 person and students of class XI MIPA 1 with 30 people as sources of practicality and effectiveness test data. The instrument of validity is a validation sheet, practicality, namely teacher and student response questionnaires, and effectiveness, namely learning outcomes tests and student motivation questionnaires in chemistry learning. Results: (1) PowerPoint  iSpring Suite validity test from material experts of 3.72 and media experts of 3.63 with very valid categories, (2) average percentage of practicality based on student and teacher response questionnaires of 77.29% and 87.25% with very practical categories, 3) class completeness with a percentage of 86.67% with an increase in learning outcomes of 17% from 30% of students who did not achieve completion of learning colloidal material chemistry and increased learning motivation Students in chemistry learning with an average percentage of 5% per indicator. Based on these data, it is concluded that the PowerPoint  iSpring Suite developed with the ADDIE model is valid, practical, and effective to improve student motivation and learning outcomes.